Peranan Akuntansi Pertanggungjawaban Sebagai Alat Pengendalian Biaya Pada PT Sarana Metal Jayatama Di Surabaya - Ester Christina Akunut; Diana Zuhroh; Tjandra Wasesa; Wiratna Wiratna; Heri Toni Hendro P (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
PT Sarana Metal Jayatama is a company engaged in the supply and production of building materials. The author conducted research at this company with the aim of finding out whether the implementation of responsibility accounting as a means of cost control at PT Sarana Metal Jayatama has functioned properly in accordance with the requirements of responsibility accounting. The type of data used by the author is primary data, from the results of interviews with the finance department. Secondary data data obtained from company files. The data is then analyzed using a descriptive method, by comparing the existing data with the theory that the authors studied. In this study, several weaknesses were found in the company, namely: the preparation of the budget in this company did not reflect the principle of participation because it did not involve all existing elements and was not in accordance with what was budgeted. There is no separation of controllable and uncontrollable costs. The existing estimate code is not fully in accordance with the principles of responsibility accounting. The company also has not periodically evaluated the company's performance and inadequate accountability reports.